Catecholamine research in the 21st Century : abstracts and graphical abstracts, 10th International Catecholamine Symposium, 2012 - Eiden, Lee E. (Academic Press, 2013)
Through the use of extended graphical abstracts and some traditional text-only abstracts this collection provides, a record of and roadmap to, the research presented at The Tenth International Catecholamine Symposium (XICS) held in September of 2012. Organized around ten general themes, each is introduced by a short overview identifying interesting research programs, results and potential areas of growth. The collection is a roadmap to key research and future opportunities for new catecholamine research programs and will be of interest to neuroscientists and clinical neurologists interested.